2013
DOI: 10.1111/cla.12006
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic analysis of the megadiverse Chalcidoidea (Hymenoptera)

Abstract: Chalcidoidea (Hymenoptera) is extremely diverse with an estimated 500 000 species. We present the first phylogenetic analysis of the superfamily based on both morphological and molecular data. A web-based, systematics workbench mx was used to score 945 character states illustrated by 648 figures for 233 morphological characters for a total of 66 645 observations for 300 taxa. The matrix covers 22 chalcidoid families recognized herein and includes 268 genera within 78 of 83 subfamilies. Morphological data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
338
3
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(368 citation statements)
references
References 101 publications
(366 reference statements)
21
338
3
6
Order By: Relevance
“…Extant Hexapus morphotypes seem to represent the most ancestral pollinating agaonines of Ficus, because among other pleisiomorphic characters: 1-the females do not possess a gular bridge composed of carinated sclerite, as assumed by Rasplus et al (1988) for Agaoninae; 2-the antenna has a terminal bottom (terminal nipple), as found in Pteromalidae (Grahan, 1969), which is considered as a separate 12 th flageromere, homologous to the apical segment of Rotoitidae, and also reported for some Eucharidae (Heraty et al, 2013 and references there in). Furthermore, the female Hexapus is uniquely characterized among other Agaoninae by the possession of two independent mandibular appendages.…”
Section: Resultsmentioning
confidence: 80%
“…Extant Hexapus morphotypes seem to represent the most ancestral pollinating agaonines of Ficus, because among other pleisiomorphic characters: 1-the females do not possess a gular bridge composed of carinated sclerite, as assumed by Rasplus et al (1988) for Agaoninae; 2-the antenna has a terminal bottom (terminal nipple), as found in Pteromalidae (Grahan, 1969), which is considered as a separate 12 th flageromere, homologous to the apical segment of Rotoitidae, and also reported for some Eucharidae (Heraty et al, 2013 and references there in). Furthermore, the female Hexapus is uniquely characterized among other Agaoninae by the possession of two independent mandibular appendages.…”
Section: Resultsmentioning
confidence: 80%
“…Heraty et al (2013) and Gumovsky (2016) suggested that the other extant and fossil groups assigned to this family are likely not related to the nominal subfamily Tetracampinae. Heraty et al (2013) reported Tetracampinae as monophyletic based on 6 synapomorphies. However, none of these character states are present in Afrocampe gen. nov.…”
Section: Discussionmentioning
confidence: 97%
“…Scanning electron microscopy (SEM) was carried out in the Institute for Evolutionary Ecology NAS Ukraine (IEE, Kiev) using a Jeol JCM-6000 in a low-vacuum mode. Terminology largely follows that of Gibson (1997) and Heraty et al (2013).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations